Investigating the Impact of Pressure Relief Performance on the Occurrence of Pressure Injuries and Shoulder Pain in Wheelchair Users with Spinal Cord Injury (PRperf Study): Study Protocol for a Prospective Observational Study - Yannik Schürch; Anneke Hertig-Godeschalk; Inge Eriks-Hoogland; Anke Scheel-Sailer; Martin W. G. Brinkhof; Ursina Arnet (Methods and Protocols, 2025)
Background: Pressure injuries (PIs) and shoulder pain (SP) are frequent problems in individuals with spinal cord injury (SCI), affecting both quality of life and healthcare use. Although pressure relief (PR) is recommended to prevent PIs, it is often not performed regularly, and its long-term benefits remain unclear. Furthermore, some PR methods may contribute to SP, resulting in conflicting clinical guidelines. This study aims to objectively measure PR performance and investigate its long-term relationship with PI and SP. Methods: This study is a longitudinal observational study involving 70 manual wheelchair users with complete SCI. Over one year, participants attend five study visits to assess confounding factors such as comorbidities and shoulder range of motion. PR performance (technique, frequency, duration) is continuously monitored for three weeks after each of the first four visits using textile measurement mats, while SP is assessed weekly with a questionnaire. Causal associations with PI and SP will be examined using directed acyclic graphs and multivariable regression modelling. Results: The study is ongoing. Long-term objective data on PR performance will provide insights into its relationship with PI and SP. Conclusions: Findings will inform clinical practice and contribute to improved evidence-based PR guidelines for individuals with SCI.